Effect of nanoparticles on wettability of nanocoating on carbon steel - Johari, Norhasnidawani; Hassan, Noor Azlina; Hassan, Norita; Ani, Mohd Hanafi (OpenJournalSystems.com, 2016)
Nanocoatings plays an important role in coating industry. The solution was being prepared through copolymerization of epoxy resin hardener and with the incorporation of metal oxide nanoparticles, Zinc Oxide (ZnO) and Silica (SiO2). ZnO and SiO2 were synthesized using sol-gel. Epoxy hardener acted as host while the metal oxide nanoparticles as guest components. The formulation of nanocoatings with excellent adhesion strength and corrosion protection of carbon steel was studied. The performance of wetting ability with different medium was analysed using contact angle. Water medium showed the addition of 3wt% of hybrid between ZnO and SiO2 was the best nanocoating to form hydrophobic surface and was also the best nanocoating surface to form hydrophilic surface with vacuum oil dropping. In oil dropping, the contact angle was smaller than 90° and the water drop tends to spreads on surface.